2020
DOI: 10.1111/vde.12910
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and clinical management of auricular chondritis in a dog presenting for evaluation of severe pain

Abstract: Background The aetiology and appropriate treatment for auricular chondritis in the dog are currently unclear. This report describes a unique presentation and successful treatment of a dog with auricular chondritis. Clinical summary A 12‐year‐old, female spayed, Labrador retriever dog was presented for severe pain thought to be neurological in origin. The pain was located to the right pinna and two punch biopsies were acquired and evaluated, revealing lymphoplasmacytic to pyogranulomatous inflammation involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 2 publications
(6 reference statements)
1
12
0
Order By: Relevance
“…Cases of primary auricular and laryngeal chondritis in animals and humans are not associated with otohematoma. 1,3,6,16,18 In the pigs of this study, otohematomas were frequently observed in the nursery and progressed to a chronic form in the nursery but, most frequently, in the finishing phase. These otohematomas may have developed by self-trauma, due to irritation and pain originated from the inflammatory process.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Cases of primary auricular and laryngeal chondritis in animals and humans are not associated with otohematoma. 1,3,6,16,18 In the pigs of this study, otohematomas were frequently observed in the nursery and progressed to a chronic form in the nursery but, most frequently, in the finishing phase. These otohematomas may have developed by self-trauma, due to irritation and pain originated from the inflammatory process.…”
Section: Discussionmentioning
confidence: 65%
“…The diagnosis of auricular and laryngeal chondritis in the pigs was performed through the association of clinical, macroscopic, and microscopic findings. There are few reports of lesions restricted to the auricular cartilage in other species, such as cats, 3 dogs, 18 cattle, 1 and rats. 16 The morphologic lesions observed by us in pigs are extremely similar to those described for other species and human RP, suggesting that all of these conditions are primary lesions of the cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The term 'auricular chondritis' refers to an immunemediated inflammatory process of the auricular cartilage described in humans and other animal species, including cats and, more rarely, dogs. [1][2][3][4][5] According to the limited literature available, the disease manifests in dogs as a painful nodular swelling of one or both pinnae and is characterised histologically by necrosis of the auricular cartilage surrounded by lymphoplasmacytic and pyogranulomatous inflammation. Cartilage destruction causing ear deformity is a well-known complication of auricular chondritis in humans, yet it has never been described in dogs.…”
Section: Introductionmentioning
confidence: 99%